Imaging shapes of atomic nuclei in high-energy nuclear collisions - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Nature, 2024)
Atomic nuclei are self-organized, many-body quantum systems bound by strong nuclear forces within femtometre-scale space. These complex systems manifest a variety of shapes1-3, traditionally explored using non-invasive spectroscopic techniques at low energies4,5. However, at these energies, their instantaneous shapes are obscured by long-timescale quantum fluctuations, making direct observation challenging. Here we introduce the collective-flow-assisted nuclear shape-imaging method, which images the nuclear global shape by colliding them at ultrarelativistic speeds and analysing the collective response of outgoing debris. This technique captures a collision-specific snapshot of the spatial matter distribution within the nuclei, which, through the hydrodynamic expansion, imprints patterns on the particle momentum distribution observed in detectors6,7. We benchmark this method in collisions of ground-state uranium-238 nuclei, known for their elongated, axial-symmetric shape. Our findings show a large deformation with a slight deviation from axial symmetry in the nuclear ground state, aligning broadly with previous low-energy experiments. This approach offers a new method for imaging nuclear shapes, enhances our understanding of the initial conditions in high-energy collisions and addresses the important issue of nuclear structure evolution across energy scales.
STAR Collaboration: M.I. Abdulhamid, I.M. Deppner, Leung, Y.H. Leung, Y. Söhngen, P.C. Weidenkaff [und 294 weitere]
Online verfügbar: 06. November 2024
Gesehen am 18.09.2025